Virtual target screening reveals rosmarinic acid and salvianolic acid A inhibiting metallo- and serine-β-lactamases. Issue 6 (1st April 2018) - Yu, Zhu-Jun; Liu, Sha; Zhou, Shu; Li, Hui; Yang, Fan; Yang, Ling-Ling; Wu, Yong; Guo, Li; Li, Guo-Bo
Graphical abstract: Highlights: IFPTarget prediction led to identification of VIM-2 as a bona fide target of RA. RA is a fully reversible, substrate-competitive VIM-2 inhibitor. ITC analyses reveal the binding of RA to VIM-2 is mainly driven by enthalpy. Salvianolic acid A manifests broad spectrum β-lactamase inhibition. Abstract: Rosmarinic acid (RA), a polyphenolic phytochemical, has broad-spectrum biological and pharmacological activity. A virtual target screening method termed IFPTarget combined with enzyme inhibition assays led to the identification of the clinically relevant metallo-β-lactamase (MBL) VIM-2 as one of unexploited targets of RA. The enzyme kinetic studies indicated that RA is a fully reversible, substrate-competitive VIM-2 inhibitor. The isothermal titration calorimetry (ITC) analyses revealed that the initial binding of RA to VIM-2 is mainly due to enthalpy contribution. Further inhibition assays with RA related compounds revealed that salvianolic acid A, a derivative of RA, manifests potent inhibition to VIM-2, more interestingly, which shows inhibitory activity against the NDM-1, another clinically relevant MBL subtype, and the serine-β-lactamase TEM-1 that is structurally and mechanistically distinct from the VIM-2 and NDM-1.